Gandharvi : life of a musician - Bani Basu; Sengupta, Jayita Tr (Hyderabad Orient Blackswan, 2017)
Gandharvi: Life of a Musician tells the story of Apala, a gifted singer of Hindustani classical music, whose extraordinary gift gets buried under various familial expectations, demands and repressions. Surrounding Apala$1 (Bs story are the interlinked lives of other practitioners of music and classical art, whose lives intersect with Apala$1 (Bs in ways that profoundly affect all of them. Written in lilting prose that draws on the idioms of Hindustani classical music, Gandharvi, a modern Bengali classic, is also a celebration of the indomitable spirit of music.s
Keywords: Indian English Fiction; Indian English Novel; Bengali Tr in English